Research without Archives?: The Making and Remaking of Area Studies Knowledge of the Middle East in a Time of Chronic War - Hussein Moustafa, Laila (Archivaria, 2018)
The Middle East is home to ancient historical documents of great value to archivists and historians. Systemic violence, warfare, and political instability in the region since the invasion of Iraq in 2003 have taken a terrible toll on documents and archives as well as human life. The destruction of libraries that house primary source materials affects the creation of knowledge in Middle Eastern studies in important ways that remain to be understood. In this article, I review the extent of the damage to libraries and archives in the region since the US invasion of Iraq in 2003 and then ask: What happens to Middle Eastern studies when archives are destroyed and researchers must change their topics and methods of research? Can we create knowledge about a region when its archival resources and human informants are so endangered? If access to archival materials is essential to the very essence of Middle Eastern studies, then what is happening to that field and why should that matter to archivists? I recount anecdotal evidence of researchers changing the topics and themes of their research in response to a situation of limited access to archives and to the region, and then present outcomes of a survey I designed to understand more systematically how these problems are affecting the shape of research and knowledge about the Middle East. Finally, I present an aspirational call to the cultural heritage preservation community – researchers, archivists, and librarians – to digitize archival resources in the Middle East. RÉSUMÉ Le Moyen-Orient abrite d’anciens documents historiques de grande valeur pour les archivistes et les historiens. La violence, les guerres et l’instabilité politique systémiques dans la région depuis l’invasion de l’Iraq en 2003 ont eu de lourdes conséquences sur les documents et les archives, aussi bien que sur les vies humaines. La destruction de bibliothèques qui hébergent des sources primaires a une incidence importante dont on ne saisit pas encore l’ampleur sur la création du savoir dans les études du Moyen-Orient. Dans cet article, je fais un survol de l’étendue des dommages causés aux bibliothèques et aux archives de la région depuis l’invasion américaine de l’Iraq en 2003 pour ensuite demander : qu’arrive- t-il aux études du Moyen-Orient quand les archives sont détruites et que les chercheurs doivent changer leurs sujets et méthodes de recherche? Peut-on créer le savoir au sujet d’une région quand ses ressources archivistiques et ses informateurs humains sont si ménacés? Si l’accès aux matériaux archivistiques est essentiel à l’essence même des études du Moyen-Orient, qu’advient-il de ce domaine et pourquoi les archivistes devraient-ils s’en préoccuper? Je fournis des preuves empiriques de chercheurs qui changent leurs sujets et thèmes de recherche en réaction à l’accès limité aux archives et à la région, et je présente ensuite les résultats d’un sondage que j’ai conçu pour comprendre plus systématiquement comment ces problèmes affectent l’orientation de la recherche et du savoir au sujet du Moyen-Orient. Enfin, je lance un appel ambitieux à la communauté de la préservation du patrimoine culturel – chercheurs, archivistes et bibliothécaires – à numériser les ressources archivistiques dans le Moyen-Orient.